Association between Maternal Nutritional Status Assessed by Mid-Upper Arm Circumference (MUAC) and Infant Birth Weight - Diana, Sitti Aras; Anita, Nur; Nurfadilah, Nurfadilah (Genius Journal, 2024)
Introduction: In neonatal deaths, the WHO records an average of 18 neonatal deaths, maternal deaths in developing countries are related to pregnant women suffering from malnutrition such as KEK. Therefore, malnutrition in pregnant women must be avoided, making pregnant women a target group that requires special attention. There are countries experiencing KEK incidents in pregnant women that lead to maternal and child deaths, while Indonesia is one of the parameters for determining the nutritional status of pregnant women. Nutritional status greatly influences the growth and development of the fetus. Factors related to the nutritional status of pregnant women include maternal knowledge, maternal age, and economic status; these three aspects play a crucial role in meeting nutritional needs and making decisions related to nutritional status. Objective: This study aims to determine the relationship between nutritional status in pregnant women based on LILA (Upper Arm Circumference) measurements and birth weight. Method: This research uses a cross-sectional study approach. The population in this study consists of those who have given birth from 2021 to 2023 in the working area of Puskesmas Banggae 1. Sampling was conducted using the Total Sampling technique, with a sample size of 88 respondents. The instrument used for the independent and dependent variables was a checklist, specifically the Spearman Correlation test. Result: The Spearman Correlation test yielded a significance value of 0.000, less than 0.05, indicating a relationship. Conclusion: Thus, there is a relationship between Upper Arm Circumference and Birth Weight.